Diagnostic challenges in movement disorders: Sensory Ataxia Neuropathy Dysarthria and Ophthalmoplegia (SANDO) syndrome. (30th August 2013) - Lovan, Alyson; Haq, Ihtsham ul; Balakrishnan, Nikhil
Abstract : A woman in her early 60s presented to our Movement Disorders Centre with a 5-year history of progressive peripheral neuropathy, gait instability with falls, blurred vision, cognitive impairment and tremors. The patient was found to have profound sensory ataxia, chronic ophthalmoplegia, dementia with significant deficits in registration and construction and bilateral resting tremor of the hands. Investigations revealed an unremarkable MRI of the brain, negative cerebrospinal fluid studies, and unremarkable chemistries. Nerve conduction studies found a severe sensorimotor axonal polyneuropathy. Genetic testing revealed a compound heterozygous mutation in the POLG1 gene consistent with the diagnosis of Sensory Ataxia Neuropathy Dysarthria and Ophthalmoplegia (SANDO) syndrome.